The Underlying Mechanisms of Psychological Resilience on Emotional Experience: Attention-Bias or Emotion Disengagement - Yi, Feng; Li, Xiaofang; Song, Xiaolei; Zhu, Lei (Frontiers in Psychology, 2020)
Psychological resilience is consisted of social resources and protective factors for individuals against negative effects, and could influence the process of meta-cognition of individuals in response to emotion feelings. However, individuals with high or low resilience may produce various emotional experiences when facing the same events. According to the emotional input-output model, the different impacts of resilience on emotional experience may be caused during the process of receiving or disengaging stages. In order to figure out this problem more clearly, three experiments were conducted in the present study. The Experiment 1 was designed to explore whether positive and negative emotions were associated with higher or lower levels of resilience. The aims of Experiments 2 and 3 were to test at which stage the different emotional experiences were caused by high or low resilience of individuals. The results showed that individuals with low resilience were more likely to feel more negative and less positive emotions, and the resilience was significantly negatively associated with anxiety or depression. However, there was no difference in the stage of receiving of emotional information between high and low resilient individuals, but differ in the ability of disengagement from emotional information, both positive and negative, the individuals with high resilience were more faster. These findings were discussed in the context of different theories about the relationship between resilience and emotional experience.